2022
DOI: 10.3390/s22031264
|View full text |Cite
|
Sign up to set email alerts
|

External Auditory Stimulation as a Non-Pharmacological Sleep Aid

Abstract: The increased demand for well-being has fueled interest in sleep. Research in technology for monitoring sleep ranges from sleep efficiency and sleep stage analysis to sleep disorder detection, centering on wearable devices such as fitness bands, and some techniques have been commercialized and are available to consumers. Recently, as interest in digital therapeutics has increased, the field of sleep engineering demands a technology that helps people obtain quality sleep that goes beyond the level of monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…[ 18 19 ] White noise, a sound with uniform frequency in the range of human hearing (20–20,000 Hz), refers to random sounds whose power spectral density is evenly distributed throughout the frequency domains, such as rain sound, wind sound, water flow sound, and marine sound. [ 20 ] The study has found that[ 21 22 ] white noise intervention can effectively reduce patients’ sensitivity to ambient noise and effectively improve the subjective sleep quality of patients. Adequate sleep promotes the recovery of individual spirit and physical strength, playing a very important role in the rehabilitation of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 19 ] White noise, a sound with uniform frequency in the range of human hearing (20–20,000 Hz), refers to random sounds whose power spectral density is evenly distributed throughout the frequency domains, such as rain sound, wind sound, water flow sound, and marine sound. [ 20 ] The study has found that[ 21 22 ] white noise intervention can effectively reduce patients’ sensitivity to ambient noise and effectively improve the subjective sleep quality of patients. Adequate sleep promotes the recovery of individual spirit and physical strength, playing a very important role in the rehabilitation of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies to date have focused mostly on sleep analysis, and systematic assessment of other physiological indices and behaviors will need to be performed to answer this question. Apart from genetic factors, environmental factors also exert major influences on sleep [37 42]. All animal studies to date have been conducted under baseline conditions, whereas humans experience many stressful challenges throughout their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…From the initial idea of digitalizing CBT, DTx have evolved and continue to expand the range of embedded digital interventions and targeted areas. In Table 1 we compiled a nonexhaustive list of references across a variety of indications where DTx are currently developed, used or foreseen to play a key role for patients 2–41 . This illustrates why their development is associated with significant promise, in particular for tackling the continuously growing burden of chronic diseases 42 …”
Section: Category Target References Comment Type Publication Yearmentioning
confidence: 99%